Rainwater management interventions—The 'happy strategies' game - Duncan, Alan J. (2011)
One project of the Nile Basin Development Challenge (http://nilebdc.org) aims to match land and water 'practices' and interventions to the needs of specific landscapes. In 2011, we experimented with a game - modeled on the 'happy families' childrens' game - to discuss the challenges involved. In this video, Alan Duncan (ILRI) and other game members explain the results of a game played at the 3rd International Forum on Water and Food in November 2011. The game used a fictional landscape derived from real NBDC sites in Ethiopia.